A Multi‐Omics Analysis of Glycine max Leaves Reveals Alteration in Flavonoid and Isoflavonoid Metabolism Upon Ethylene and Abscisic Acid Treatment. Issue 7 (7th March 2018) - Gupta, Ravi; Min, Cheol Woo; Kramer, Katharina; Agrawal, Ganesh Kumar; Rakwal, Randeep; Park, Ki‐Hun; Wang, Yiming; Finkemeier, Iris; Kim, Sun Tae
Abstract: Phytohormones are central to plant growth and development. Despite the advancement in our knowledge of hormone signaling, downstream targets, and their interactions upon hormones action remain largely fragmented, especially at the protein and metabolite levels. With an aim to get new insight into the effects of two hormones, ethylene (ET) and abscisic acid (ABA), this study utilizes an integrated proteomics and metabolomics approach to investigate their individual and combined (ABA+ET) signaling in soybean leaves. Targeting low‐abundance proteins, our previously established protamine sulfate precipitation method was applied, followed by label‐free quantification of identified proteins. A total of 4129 unique protein groups including 1083 differentially modulated in one (individual) or other (combined) treatments were discerned. Functional annotation of the identified proteins showed an increased abundance of proteins related to the flavonoid and isoflavonoid biosynthesis and MAPK signaling pathway in response to ET treatment. HPLC analysis showed an accumulation of isoflavones (genistin, daidzein, and genistein) upon ET treatment, in agreement with the proteomics results. A metabolome analysis assigned 79 metabolites and further confirmed the accumulation of flavonoids and isoflavonoids in response to ET. A potential cross‐talk between ET and MAPK signaling, leading to the accumulation of flavonoids and isoflavonoids in soybean leaves is suggested.